Antioxidant, α-glucosidase and nitric oxide inhibitory activities of Phyllanthus acidus L. leaves in correlation with their metabolites using ¹H-NMR- and LCMS-based metabolomics - Abd Ghafar, Siti Zulaikha (2019)
Phyllanthus acidus L. also known as star gooseberry, is a well-known medicinal plant used as a traditional remedy. Different parts of this plant have been used to manage several disorders associated with oxidative stress diseases, including inflammation. Solvent polarity has a significant influence on the extraction of metabolites and need to be optimized. In this study, the total phenolic (TPC), antioxidant (DPPH and nitric oxide scavenging), α-glucosidase and nitric oxide (NO) inhibitory activities from two parts (leaf and fruit) of P. acidus extracted with various ethanol ratios (0, 50 and 100%) were evaluated. Furthermore, proton nuclear magnetic resonance (¹H-NMR)- and liquid chromatography mass spectrometry (LCMS)-based metabolomics approaches were applied to identify the metabolites in the active parts of P. acidus extracted with various ethanol ratios. To support the identification of compounds, correlation analysis was performed with the ¹H-NMR- and LCMS data. The results showed that leaf extraction with 50% ethanol gave the most active extract with the lowest IC50 value for α-glucosidase with 1.53 μg/mL. It also showed moderate NO scavenging and inhibitory activities (IC50 = 158.17 and 180.06 μg/mL, respectively) as well as the highest TPC with 6.92 mg GAE/g dried sample. The 50% ethanol extract from the fruit had the highest TPC, DPPH free radical scavenging, NO scavenging, and α-glucosidase and NO inhibitory activities with values of 3.20 mg GAE/g dried sample, 48.41%, 49.39%, 2.44 μg/mL and 43.30%, respectively. Both metabolomics approaches showed different analytical selectivities and sensitivities. In total, 27 metabolites were tentatively identified based on the ¹H-NMR characteristics including phenolics, flavonoids, sugars, amino acids and organic acids compound groups. Using LCMS, 39 metabolites were detected and identified, which include derivatives of quercetin, kaempferol, epicatechin, coumaric, and cinnamic acids. Based on multivariate analysis, partial component analysis (PCA) of both the ¹H-NMR- and LCMS databases revealed clear separation between the P. acidus extracts. The partial least square analysis (PLS) biplot based on the ¹H-NMR data showed that the metabolites that contributed to α-glucosidase and nitric oxide (NO) inhibitory activities were kaempferol, quercetin, myricetin, phyllanthusol A, phyllanthusol B, chlorogenic, cinnamic and ellagic acids, while according to the PLS biplot for the LCMS data, the metabolites that correlated to bioactivities were the derivatives of kaempferol, quercetin, catechin, and coumaric, caffeic, quinic, citric, ellagic and malic acids. Additionally, the ¹H-NMR and LCMS correlations allowed the tentative identification of caffeoyl glucarate, pcoumaroyl glucarate, mucic acid, epigallocatechin, catechin-3'-methyl ether, kaempferol-3-glucoside-7-rhamnoside, epicatechin, phyllanthusiin E, quercetin-3-O-rhamnoside, kaempferol-3-rhamnoside-4'-xyloside and peonidin-3-glucoside as metabolite signals with highly positive correlation. In conclusion, the 50% ethanol extract from the P. acidus leaves showed antioxidant activity, a high TPC, and substantial inhibition of α-glucosidase and NO, which strengthened its traditional claim. The present study shows that the combination of ¹H-NMR- and LCMS-based metabolomics would be the best strategy for improving the discovery and identification of metabolites from P. acidus extracts and established the extract that possesses the best antioxidant, anti-diabetic, and anti-inflammatory properties.